The Relationship between Career Interests and Academic Achievements in English, Mathematics, and Science of Grade 10 Students - Nieva, Alvin (International Journal of Arts, Sciences and Education, 2022)
This study examined the predictive influence of career interests on the academic achievements of 257 grade 10 students in English, Mathematics, and Science using locally-developed measures. Specifically, this research sought to answer the question: How significant are the dimensions of career interests in predicting the academic achievements of grade 10 students in English, Mathematics, and Science? The self-enhancement model was used as a research framework, while a cross-sectional, predictive study was used as a research design. Data were analyzed using both descriptive and inferential statistics. Based on the results of multiple regression analysis, an occupational group that engages in explicit, ordered, and systematic manipulation of data consistently positively predicts academic achievements in English, Mathematics, and Science. While an occupational group that works in the production, quality assurance, and maintenance of products, operations, and services consistently predicts academic achievements in English, Mathematics, and Science. Furthermore, an occupational group that develops and designs manufactured products and creates two- and three-dimensional models and animation predicted academic achievements in English and Mathematics but not in Science. Although it is considered a crucial period for Filipino adolescents to select a specific track in the middle school that matches their interests and capabilities, most of them are still quite uncertain of the occupational groups they would like to pursue. This stability of adolescents’ career interests has essential implications for the conceptualization and practice of career guidance in schools.